The zeronauts : breaking the sustainability barrier - Elkington, John, 1949- (Routledge, 2012)
"In the last century, astronauts (meaning space sailors) launched into the heavens, in search of new worlds to colonize-their adventures helping to catalyze the evolution of everything from non-stick frying pans and minicomputers to satellite telecommunications. Their work forced our species to recognize that our Earth is a very rare planet indeed and our only home for the foreseeable future. Now a new wave of explorers, adventurers and entrepreneurs is pioneering novel ways to create wealth in tune with the twenty-first century reality of a human population pushing towards ten billion people by mid-century and with key elements of the planet's biosphere already coming apart at the seams. These are the Zeronauts. Featuring contributions by twenty-five of the world's leading innovators and drawing on interviews and surveys of many more, the book showcases the pioneers that are at the cutting edge of the global sustainability movement, which the author, John Elkginton, has helped create and lead over several decades. Elkington introduces the emerging disciplines of zero-impact design, engineering and management-through the personal experiences and reflections of the leading practitioners putting us on a path to a zero impact economy: zero risk zero emissionszero pollution and wastezero biodiversity losszero population growth.Leading Zeronauts explain how they came to wake up to the challenges they speak about the mistakes they have made along the way and the lessons they have learned in the process offering their advice on how we can get others to the same point in terms of thinking and action. From this, Elkington distils a concise set of rules for success. Concluding with recommendations for governments, investors, innovators and educators, the book shares the lessons learned from scores of people worldwide who are helping define the scale of the challenges our species now faces and, crucially, developing and deploying at scale some of the solutions that will provide the building-blocks of tomorrow's economies and the foundations for some of the future's greatest fortunes"--